Rapid screening and quantification of cyromazine, melamine, ammelide, ammeline, cyanuric acid, and dicyandiamide in infant formula by ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry and triple quadrupole mass spectrometry. (September 2015) - Meng, Zhe; Shi, Zhihong; Liang, Shuxuan; Dong, Xinfeng; Lv, Yunkai; Sun, Hanwen
Abstract: In the past few years, special concern for triazine pesticide cyromazine (CYRO) and its metabolites melamine (MM), ammelide (AMD), ammeline (AMN), cyanuric acid (CA), and dicyandiamide (DCD) residues has arisen in the food safety field on infant foods. In this work, screening and confirmation for infant milk powder samples were performed by quadrupole time-of-flight mass spectrometry (QTOF-MS). An accurate mass database was established. The matrix-matched internal standard calibration curves of UPLC–MS/MS were linear, with correlation coefficient (r 2 ) higher than 0.994. The limits of quantification (LOQ) were 1.6, 5.0, 16.5, 10.0, 66.4, and 66.4 μg/kg for CYRO, MM, AMD, AMN, CA, and DCD, respectively. The average recoveries ranged from 64.8 to 103%. The retention time, intra- and inter-day precisions (relative standard deviation, RSDs) of 6 analytes were in the range of 0.02–0.05%, 2.4–6.1%, and 7.2–11.2%, respectively. CYRO and MM residues in some infant milk powder samples were confirmed. Quantitation of positive samples was performed using the internal standard method and six-point matrix-matched calibration curves. The content for CYRO in all 8 samples and MM in 4 samples were in the range of 3.5–45 μg/kg and 8–25 μg/kg, respectively. The method developed for the first time has high sensitivity, can be used as an effective tool for rapid screening and highly sensitive multiresidue determination of CYRO, MM and their metabolites AMD, AMN, and CA as well as DCD in milk powder samples. Highlights: Screening and confirmation of cyromazine, melamine, and their four metabolites in milk powder were performed. The fragmentation pathways and mass databases were established by QTOF-MS. The UPLC–MS/MS method has good linearity, high sensitivity, and satisfactory precision. The method can be used for rapid screening and quantification of the six residues in milk power samples.